Signature of climatic differentiation on mitochondrial DNA of Drosophila sturtevanti - Zorzato, Samara Videira [UNESP]; Yassin, Amir; Madi-Ravazzi, Lilian [UNESP] (Taylor & Francis, 2022)
Pleistocene climatic changes have played a major role in the evolution of Brazilian Atlantic Forest and South America biodiversity but their impacts on the genetic structure of widely distributed species remain unclear. Here, we investigate mitochondrial DNA (mtDNA) diversity in 21 geographical populations of Drosophila sturtevanti, Nucleotide sequences of the cytochrome C oxidase subunits I and II genes (COI and COII, respectively) from 163 individuals, showed a significant north-south structure, in spite of an overall low level of variation. The haplotypes clustered in three groups that showed strong correlations with geographical and climatic variables, suggesting that local adaptations might have contributed to differentiation within the species. Coalescent-based analyses indicated that the three clusters have differentiated nearly ∼17.000 years ago, suggesting a major role for Pleistocene changes in shaping current day distributions and differentiation of widespread Neotropical species.
Keywords: Adaptation; mtDNA; neotropics; paleoclimate; phylogeography; saltans group